ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN LAMA PERSALINAN KALA II DI TPMB Hj. MARDIAWATI, S.ST., M.Kes. - Tahir, Suriani; Dahniar, Dahniar; Irfana, Irfana (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Childbirth is a critical period for women who contribute to maternal morbidity and mortality in developing countries, one of which is Indonesia. One of the complications in childbirth is prolonged labor, which is the direct cause of childbirth complications with an incidence of 69,000 or 2.8% of deaths from all maternal deaths worldwide. The purpose of analyzing the factors associated with the length of Labor kala II. Analytical survey method with cross sectional study approach chi Square data analysis technique with dichotomic nominal scale. a total of 128 respondents using the Isaac and Michael formula, the results of X2 count 0.021 is smaller than x2 table 3.841 and the value of 0.884 is greater than the value of 0.05 show that there is no significant relationship between the age of the mother with the length of Labor kala II, the results of X2 count 24.522 is, the results of X2 count 0.992 is smaller than x2 table 3.841 and the value of 0.319 is greater than the value of ? 0.05 indicate that there is no significant relationship between maternal education with the length of Labor Time II, the result of x2 count 1.911 is smaller than x2 table 3.841 and the value of ? 0.167 is larger than ? 0.05 indicates that there is no significant relationship between the mother's work with the length of labor in Stage II,the result of x2 count 0.009 is smaller than x2 table 3.841 and the value of ? 0.925 is larger than ? 0.05 indicates that there is no significant relationship between fetal weight with the length of labor in Stage II. The conclusion that the parietas of maternity mothers can be an indicator for the occurrence of long Labor Phase II that can be anticipated earlier by minimizing complications during childbirth. ABSTRAKMasa persalinan merupakan masa kritis bagi perempuan yang berkotribusi terhadap angka kesakitan dan kematian ibu di negara berkembang salah satunya Indonesia. Salah satu komplikasi pada persalinan adalah persalinan lama,yang merupakan penyebab langsung komplikasi persalinan dengan jumlah kejadian sebesar 69.000 atau 2,8% kematian dari semua kematian ibu di seluruh dunia. Tujuan untuk menganalisis faktor faktor yang berhubungan dengan lama persalinan kala II. Metode survey analitik dengan pendekatan cross sectional study teknik analisa data Chi Square dengan skala nominal dikotomik. sebanyak 128 responden dengan menggunakan rumus Isaac and Michael, Hasil x2 hitung 0,021 lebih kecil daripada x2 tabel 3,841 dan nilai ? 0,884 lebih besar daripada ? 0,05 menunjukkan bahwa tidak ada hubungan yang signifikan antara umur ibu dengan lama persalinan kala II, hasil x2 hitung 24,522 lebih besar daripada x2 tabel 3,841 dan nilai ? 0,000 lebih kecil daripada ? 0,05 menunjukkan bahwa terdapat hubungan yang signifikan antara paritas ibu dengan lama persalinan kala II, hasil x2 hitung 0,992 lebih kecil daripada x2 tabel 3,841 dan nilai ? 0,319 lebih besar daripada ? 0,05 menunjukkan bahwa tidak ada hubungan yang signifikan antara pendidikan ibu dengan lama persalinan kala II, hasil x2 hitung 1,911 lebih kecil daripada x2 tabel 3,841 dan nilai ? 0,167 lebih besar daripada ? 0,05 menunjukkan bahwa tidak ada hubungan yang signifikan antara pekerjaan ibu dengan lama persalinan kala II,hasil x2 hitung 0,009 lebih kecil daripada x2 tabel 3,841 dan nilai ? 0,925 lebih besar daripada ? 0,05 menunjukkan bahwa tidak ada hubungan yang signifikan antara berat badan janin dengan lama persalinan kala II. Kesimpulan bahwa parietas ibu bersalin dapat menjadi indikator untuk terjadinya lama persalinan kala II yang dapat diantasipasi lebih dini dengan meminimalkan komplikasi pada saat bersalin.